Eine effektive Grundrente ermöglicht notwendige Rentenreformen - Peter Haan (Wirtschaftsdienst, 2024)
– In the coming years, the pension system in Germany will face financial challenges. The insurance within pension system must also be strengthened, especially given that the risk of old-age poverty has increased over the years. An effective basic pension that guarantees a minimum amount and is anchored in the pension system would be an important step in reducing poverty in old age. An effective basic pension is also an important prerequisite for implementing necessary pension reforms in Germany, such as increasing the retirement age or stronger (funded) private provision.
Keywords: H55; J11; J26; 330; Gesetzliche Rentenversicherung; Mindestrente; Deutschland; Gesetzliche Rentenversicherung; Mindestrente; Deutschland